Efficacy of artemether-lumefantrine and dihydroartemisinin-piperaquine and prevalence of molecular markers of anti-malarial drug resistance in children in Togo in 2021 - Ameyo Monique Dorkenoo; Marian Warsame; Essoham Ataba; Manani Hemou; Kossi Yakpa; Efoe Sossou; M’badi Mitigmsagou; Carmel Diwaba Teou; Emmanuelle Caspar; Laurence Ma; Koffi Edem Djadou; Tinah Atcha-Oubou; et al. (Malaria Journal, 2024)
Abstract Background Artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP) are the currently recommended first- and second-line therapies for uncomplicated Plasmodium falciparum infections in Togo. This study assessed the efficacy of these combinations, the proportion of Day3-positive patients (D3 +), the proportion of molecular markers associated with P. falciparum resistance to anti-malarial drugs, and the variable performance of HRP2-based malaria rapid diagnostic tests (RDTs). Methods A single arm prospective study evaluating the efficacy of AL and DP was conducted at two sites (Kouvé and Anié) from September 2021 to January 2022. Eligible children were enrolled, randomly assigned to treatment at each site and followed up for 42 days after treatment initiation. The primary endpoint was polymerase chain reaction (PCR) adjusted adequate clinical and parasitological response (ACPR). At day 0, samples were analysed for mutations in the Pfkelch13, Pfcrt, Pfmdr-1, dhfr, dhps, and deletions in the hrp2/hrp3 genes. Results A total of 179 and 178 children were included in the AL and DP groups, respectively. After PCR correction, cure rates of patients treated with AL were 97.5% (91.4–99.7) at day 28 in Kouvé and 98.6% (92.4–100) in Anié, whereas 96.4% (CI 95%: 89.1–98.8) and 97.3% (CI 95%: 89.5–99.3) were observed at day 42 in Kouvé and Anié, respectively. The cure rates of patients treated with DP at day 42 were 98.9% (CI 95%: 92.1–99.8) in Kouvé and 100% in Anié. The proportion of patients with parasites on day 3 (D3 +) was 8.5% in AL and 2.6% in DP groups in Anié and 4.3% in AL and 2.1% DP groups in Kouvé. Of the 357 day 0 samples, 99.2% carried the Pfkelch13 wild-type allele. Two isolates carried nonsynonymous mutations not known to be associated with artemisinin partial resistance (ART-R) (A578S and A557S). Most samples carried the Pfcrt wild-type allele (97.2%). The most common Pfmdr-1 allele was the single mutant 184F (75.6%). Among dhfr/dhps mutations, the quintuple mutant haplotype ...